Hydrogen reduction of silicon tetrachloride in low temperature non-equilibrium plasma of induction RF discharge - Deryzemlia, A.N.; Yevsiukov, A.I.; Radchenko, V.I.; Khizhnyak, D.A.; Kryshtal, P.G.; Zhuravlov, A.Yu.; Shijan, A.V.; Strigunovskiy, S.V.; Pelypets, Yu.A.; Shirokov, B.M. (Вопросы атомной науки и техники, 2019)
In this work, silicon is obtained by plasma-chemical reduction of silicon tetrachloride in an argon-hydrogen low- temperature nonequilibrium plasma. It is shown that in the investigated range of process parameters, the energy cost of producing one kilogram of silicon is in the range of 150…190 kW/h with a silicon yield of ~ 85 %. This cost reduction in the plasma-chemical process is associated with the transfer of electricity directly into the gas-vapor mixture. In addition, carrying out the recovery process under nonequilibrium conditions leads to the formation of atomic hydrogen in the discharge. Отримано кремній шляхом плазмохімічного відновлення тетрахлориду кремнію в аргон-водневій низькотемпературній нерівноважній плазмі. Показано, що в дослідженому диапазоні параметрів процесу енергетичні витрати на отримання одного кілограма кремнію знаходиться в межах 150…190 кВт/ч при виході кремнію ~ 85 %. Таке зниження витрат у плазмохімічному процесі пов'язане з введенням електроенергії безпосередньо в парогазову суміш. Крім того, проведення процесу відновлення в нерівноважних умовах призводить до утворення в розряді атомарного водню. Получен кремний путем плазмохимического восстановления тетрахлорида кремния в аргон-водородной низкотемпературной неравновесной плазме. Показано, что в исследуемом диапазоне параметров процесса энергетические затраты на получение одного килограмма кремния находятся в пределах 150…190 кВт/ч при выходе кремния ~ 85 %. Такое снижение затрат в плазмохимическом процессе связано с введением электроэнергии непосредственно в парогазовую смесь. Кроме того, проведение процесса восстановления в неравновесных условиях приводит к образованию в разряде атомарного водорода.